Tuberculosis and Diabetes Mellitus Comorbidity among the Ageing Population: A Threat to the Public Health System of Nepal - Maharjan, Bijay; Chalise, Hom Nath; Thapa, Mamta (Journal of Nepal Health Research Council, 2018)
Ageing population is attributable to the growing trend of diabetes mellitus. Diabetic patients are three times greater risk of developing tuberculosis. The review aims to describe the state of tuberculosis and diabetes mellitus comorbidity, risk factors for the comorbidity from the perspective of the ageing in Nepal. It is a systematic narrative review of literature in Google Scholar and Pubmed. At first, title and abstract of an article was reviewed for relevance, and then full article was reviewed for validity. The secondary data was retrieved from the Central Bureau of Statistics of Nepal and WHO, and analysed in the Ms-Excel. In Nepal, the population is ageing. The risk factors associated with diabetes are escalating. On the other hand, tuberculosis is endemic and about 45% of the Nepalese people are infected with tuberculosis bacteria. These circumstances have laid the foundation that fosters tuberculosis and diabetes co-epidemic in the future. The clinical management of patients with the comorbid condition is a difficult task because diabetes and tuberculosis interact with each other, one worsening the other. The upsurge of the co-morbidity needs the provision of more health services threatening the public health system of Nepal. It is fundamental to create a mechanism to integrate diabetes and tuberculosis program such as screening, diagnosis and management of the both diseases at the all levels of health service delivery. Furthermore, increase awareness of healthy lifestyle and the prevention of the risk factors for tuberculosis and diabetes could reduce the occurrence of the comorbidity in the future.